OTORITAS AGAMA ULAMA PEREMPUAN: Studi terhadap Kepemimpinan Fauziah Fauzan di Perguruan Diniyyah Puteri Padang Panjang, Sumatera Barat, Indonesia - Ilham Mundzir; Yusron Razak (Kafa`ah: Journal of Gender Studies, 2020)
Examining about relationship between religious authorities and gender, this article is focused on portraying the life and career of a female cleric in West Sumatra, contemporary Indonesia. This research was conducted by interviewing and using ethnographic techniques towards the leadership of Fauziah Fauzan, Director of Diniyyah Puteri in Padang Panjang City. The findings of this study indicate that religious knowledge was not the only capital to be a female cleric, while leadership played an important role for the formation of women’s religious authority. By combining his ascribed authority with the ability to lead (leadership), Fauziah’s religious authority gained recognition by the community and the state. The longer experience of general education, compared to the background of his religious education, did not become an obstacle for Fauziah in contesting to obtain the religious authority which has traditionally been dominated by men. Using the two main theories of feminism, namely agency and freedom, as used by Saba Mahmood, this article was not only limited to help to understand how Fauziah’s achievements reflected the experience of a Muslim woman turning herself into an ethical subject and could be a community leader, but also a community leader. Her leadership was an alternative model of how a woman could gain religious authority in a Muslim society which was changing due to modernization.